Implementasi Model Cooperative Learning Teams Games Tournaments (TGT)- Giant Ladder Snake dalam Pembelajaran Berbicara Bahasa Arab - Siti Wahyuni (LPPM Institut Pesantren KH. Abdul Chalim, 2023)
The classroom action research discusses the application of cooperative learning Teams Games Tournament (TGT)- Giant Ladder Snake to improve students’ Arabic speaking skills. The study involved students of class IX IPA 3 at SMAIT As-Syifa Boarding School Wanareja Subang. The research instrument used to collect data consisted of student activity observation sheets and an oral test of speaking skills. The study was conducted in two cycles by following several research steps proposed by Kemmis & Taggart (1999). Each cycle consisted of planning, implementation, observation, and reflection steps. The result of this study were a cooperative learning Teams Games Tournament (TGT)- Giant Ladder Snake was effective in learning Arabic, especially in learning speaking skills, because it is seen from the increase in the percentage of student activity from cycle I to cycle II. Based on the percentage results, the initial student activity level was 73%, increasing to 94.2%. There was also an increase in the percentage of students' oral test scores, in the first cycle which was 35.51% to 85.2% in the second cycle.